2020
DOI: 10.1021/acs.energyfuels.0c02036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Maturity on Pore Type and Size in Transitional Shale Reservoirs: An Example from the Upper Paleozoic Shanxi Formation, Ordos Basin, China

Abstract: The impacts of thermal maturity on the pore size, volume, and distribution in transitional shale are recognized. Combined with previous research results, Shanxi shale of the upper Paleozoic formation in the Ordos Basin, China, was selected to identify the evolution of shale pore size and types, and clarify the factors affecting the pore development. Samples of Shanxi shale from the northeastern Ordos Basin (NOB) were selected for experimental analysis, including total organic carbon (TOC) content, vitamin refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Generally, when the TOC content of shale samples is higher than ∼5%, the meso- and macropore volumes of shale samples decrease with an increasing TOC content (panels b and c of Figure ). The decrease of meso- and macropore volumes with an increasing TOC content might be due to the infilling of organic matter in mineral pores and compaction . Shale samples with a high TOC content are more ductile and could be more easily compacted, reducing the pore volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, when the TOC content of shale samples is higher than ∼5%, the meso- and macropore volumes of shale samples decrease with an increasing TOC content (panels b and c of Figure ). The decrease of meso- and macropore volumes with an increasing TOC content might be due to the infilling of organic matter in mineral pores and compaction . Shale samples with a high TOC content are more ductile and could be more easily compacted, reducing the pore volume.…”
Section: Discussionmentioning
confidence: 99%
“…The nanopore structure of shales is of great significance for the storage, enrichment, and transport of shale gas. , The characterization and controlling factors for the development of nanopores in transitional shale samples have been extensively studied and reported by previous studies. , Clays are the principal minerals in most transitional shales, followed by quartz, ,, and the clay mineral content is one of the most important factors that influences the pore volume of transitional shale samples. ,,,,,, For transitional shale samples in Shanxi Formation, Xue et al reported that compaction was the main factor that reduced the pore volume of shale samples with different burial depths . The clay mineral content of shale samples from Benxi Formation is much higher than that of Shanxi and Taiyuan Formation shales, which might be related to the sedimentary environments and diagenesis processes. , The effect of compaction on the pore volume of Benxi Formation shale samples might be more evident than that on the pore volume of Shanxi Formation shale, because clay mineral is more ductile than quartz, while the gas content of Benxi Formation shale samples is much higher than that of Shanxi Formation shale, which might make the effect of compaction on the pore volume less evident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributors to Pore Development. Researchers have concluded that the pore structure of organic-rich shale is generally governed by diagenesis, organic matter, mineral components, thermal maturity, kerogen type, etc., depending on specific geological conditions [14,23,[53][54][55][56][57]. Shale lithofacies have important controls on porosity and pore structure due to different sedimentary environments and mineralogical variations [19,51,[58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Organic matter-hosted pores have been identified as an important pore system in gas shales [9,[14][15][16][17][18]. Thermal maturity has been considered by previous studies as one of the critical controllers of organic pore growth [1,13,[19][20][21][22][23]. Researchers have tried to restore the hydrocarbon generation process and associated organic pore growth through pyrolysis, which can cover the weakness of measurements mentioned above in pore system characterization and prediction [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%